Reliability of High-Frequency Earth Meters in Measuring Tower-Footing Resistance: Simulations and Experimental Validation - Renan Segantini; Rafael Alipio; José O. S. Paulino (Energies)
This paper presents a comprehensive assessment of the accuracy of high-frequency (HF) earth meters in measuring the tower-footing ground resistance of transmission line structures, combining simulation and experimental results. The findings demonstrate that HF earth meters reliably estimate the harmonic grounding impedance (<semantics>R25kHz</semantics>) at their operating frequency, typically 25 kHz, for a wide range of soil resistivities and typical span lengths. For the analyzed tower geometries, the simulations indicate that accurate measurements are obtained for adjacent span lengths of approximately 300 m and 400 m, corresponding to configurations with one and two shield wires, respectively. Acceptable errors below 10% are observed for span lengths exceeding 200 m and 300 m under the same conditions. While the measured <semantics>R25kHz</semantics> does not directly represent the resistance at the industrial frequency, it provides a meaningful measure of the grounding system’s impedance, enabling condition monitoring and the evaluation of seasonal or event-related impacts, such as damage after outages. Furthermore, the industrial frequency resistance can be estimated through an inversion process using an electromagnetic model and knowing the geometry of the grounding electrodes. Overall, the results suggest that HF earth meters, when correctly applied with the fall-of-potential method, offer a reliable means to assess the grounding response of high-voltage transmission line structures in most practical scenarios.